The Antecedents of Digital Entrepreneurial Intention Among Management Students in Banten - Oscar Jayanagara; Geovani Filbert Kwan (Universitas Pelita Harapan, 2026)
The aim of this research is to analyze the influence of entrepreneurial education and the theory of planned behavior on digital entrepreneurial intention at universities in Banten. The method used in this research is quantitative with a purposive sampling method. In this research, the subjects were 230 respondents consisting of active management students. Data analysis in this study used the Smart PLS application Version 4.0. and used partial least squares-structural equation modeling (PLS-SEM). This research has the results that Attitude toward Behavior 0.167, Subjective Norm 0.158, Perceived Behavioral Control 0.132, and Entrepreneurial Education 0.163, have a positive and significant influence on Digital Entrepreneurial Intention. R2 is 0.130 in low category. According to the managerial implication Universities located in Banten can provide facilities that bring together fellow management students interested in Digital Entrepreneurship, also can provide students with more knowledge about Digital Entrepreneurship, such as seminars.